Modified nano zero-valent iron with core-shell structure and preparation method thereof and application thereof in catalytic degradation of wastewater containing perchlorate

By forming a core-shell structure on nano zero-valent iron, combined with the combination of manganese salt and activated carbon, the problems of low efficiency and high cost in the treatment of perchlorate-contaminated wastewater are solved, and efficient catalytic degradation is achieved Effect.

CN118637735BActive Publication Date: 2024-12-24HUNAN ACAD OF ENVIRONMENTAL PROTECTION SCI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410035160.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-10
Publication Date
2024-12-24
Estimated Expiration
2044-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove perchlorate-contaminated wastewater, especially in the production wastewater of fireworks and firecrackers with complex components. Traditional methods have problems such as low efficiency, high cost, and difficulty in regeneration.

Method used

Modified nano zero-valent iron with core-shell structure is used. By adding nano zero-valent iron to manganese salt solution to react, it forms manganese-encapsulated nano zero-valent iron, and combines it with activated carbon and ferrous sulfate to form a core-shell structure, which significantly improves the Its reduction adsorption properties and catalytic degradation properties can quickly release electrons at room temperature and effectively catalyze the degradation of perchlorate.

Benefits of technology

It achieves efficient removal of perchlorate, reduces reaction temperature and time, avoids the use of inorganic acids, improves the stability and dispersion performance of the material, is suitable for the treatment of complex wastewater, and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637735B_ABST
    Figure CN118637735B_ABST
Patent Text Reader

Abstract

The invention discloses a modified nano zero-valent iron with a core-shell structure, a preparation method thereof, and an application thereof in catalytic degradation of wastewater containing perchlorate, belonging to the technical field of wastewater treatment. The preparation method of the modified nano zero-valent iron with a core-shell structure comprises the following steps: (1) adding nano zero-valent iron to a manganese salt solution, reacting, and solid-liquid separation to obtain nano zero-valent iron wrapped with manganese; (2) stirring the nano zero-valent iron wrapped with manganese, activated carbon, and ferrous sulfate to obtain a modified nano zero-valent iron with a core-shell structure; the manganese salt solution is a manganese sulfate solution; the core of the modified nano zero-valent iron with a core-shell structure is nano zero-valent iron, and the shell is manganese element and activated carbon. The modified nano zero-valent iron with a core-shell structure has excellent reduction adsorption performance and catalytic degradation performance, and can effectively catalytically adsorb perchlorate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a modified nanometer zero-valent iron with a core-shell structure, a preparation method thereof, and an application thereof in catalytic degradation of wastewater containing perchlorate. Background Art

[0002] Perchlorate can enter the human body through drinking water and endanger human health. The main hazard is that it affects the normal function of the human thyroid gland. The reason is that the charge and ion radius of perchlorate are very close to those of iodine ions. It can compete with iodine ions and directly enter the human thyroid gland, hindering the body's absorption of iodine. It causes iodine deficiency and leads to thyroid enlargement, commonly known as "big neck disease". In addition, perchlorate dust can also irritate human mucus membranes and eyes, and after entering the human respiratory system and body, it can cause symptoms such as respiratory disorders, coughs, and liver and kidney damage.

[0003] In March 2022, the National Health Commission issued the "Quality Standard for Drinking Water" (GB 5749-2022), which for the first time included perchlorate in the control indicators and set a standard limit of 70 micrograms / liter. Subsequent testing showed that the perchlorate content in local surface waters was relatively high, showing obvious characteristics of river basin pollution. It is necessary to investigate the source and take effective measures to reduce the concentration.

[0004] Perchlorate is a typical tetrahedral structure. Because the Cl atom is +7, perchlorate has a strong oxidizing property. 4 - The energy on each chemical bond is evenly distributed, and it can exist for a long time in nature. Perchlorate is not easy to decompose at room temperature, and it is a non-volatile substance with a half-life of up to ten years in the environment. The high stability, non-volatility, high water solubility, strong oxidizing property, low adsorption, and strong mobility of perchlorate make it difficult to remove by traditional methods.

[0005] Chemical reduction is used to treat perchlorate wastewater. Some metal compounds have good catalytic activity and can be used for the chemical reduction degradation of perchlorate. This method is low-cost, simple to operate, and easy to popularize, but it has a slow reaction and low efficiency. In addition, most metal reducing agents are toxic substances and the reaction conditions are harsh.

[0006] The disadvantage of using activated carbon adsorption to treat perchlorate wastewater is that the untreated activated carbon has limited adsorption capacity for perchlorate and must undergo surface modification to improve its adsorption capacity for perchlorate. However, after surface treatment, the activated carbon will affect its adsorption of other pollutants and increase the treatment cost. It will also cause secondary pollution such as the introduction of surfactants.

[0007] The ion exchange method is used to treat perchlorate wastewater. Through the chlorine-type anion exchange resin, the perchlorate ion will exchange with the chloride ion at the exchange sites on the resin surface and in the inner pores and be adsorbed. During the ion exchange process, due to the strong interaction between perchlorate and the exchange resin, it is often difficult to replace the perchlorate adsorbed on the resin, and the resin is difficult to regenerate.

[0008] Electrochemical reduction is used to treat perchlorate wastewater. A high potential is applied to the cathode to reduce perchlorate to chloride ions, avoiding the use of catalysts. The high potential of pitting corrosion will lead to electrode consumption and promote the oxidation of chloride ions into chlorine gas. Reducing the pitting potential of metal electrodes is the key to solving the problem of zero-valent titanium in electrochemical applications. The principle of microbial reduction degradation is that under anaerobic conditions and enzyme catalysis, perchlorate ions act as electron acceptors to accept certain inorganic substances in the environment, such as zero-valent iron (Fe 0 ), H 2 , elemental sulfur or organic substances such as acetic acid, ethanol, lactic acid and other electron donors are reduced to chloride ions to achieve the purpose of biodegradation. It is still in the research stage.

[0009] Membrane separation technology is used to treat perchlorate wastewater. Membrane separation technology can effectively remove perchlorate from water bodies and plays an important role in removing perchlorate from drinking water. However, it is quite expensive, the membrane is easily contaminated and damaged, the service life is short, and the concentrated perchlorate wastewater after treatment requires subsequent treatment. Therefore, it is rarely used on a large scale.

[0010] There have been relevant studies on the use of zero-valent iron to catalyze the reduction of perchlorate wastewater, but there are common disadvantages such as the need for heating, long reaction time, the need to add inorganic acid to maintain reaction acidity, easy agglomeration of nano-iron, and low removal concentration, and there is a lack of actual industrial cases; especially for the wastewater from fireworks and firecrackers production, which contains a large amount of potassium perchlorate, sulfur, lead, copper, zinc, manganese, aluminum and other metal substances, and there are multiple interfering factors such as carbonate, sulfate, nitrate, bromate, bromide, etc., and the composition is complex, and there is a lack of an overall system treatment method.

[0011] In view of this, this application is filed. Summary of the invention

[0012] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a core-shell structured modified nano zero-valent iron and a preparation method thereof and its application in catalytic degradation of perchlorate-containing wastewater, which has excellent reduction adsorption performance and catalytic degradation performance and can effectively catalytically adsorb perchlorate.

[0013] To achieve the above object, the technical solution adopted by the present invention is:

[0014] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0015] (1) adding nano-zero-valent iron to a manganese salt solution, reacting, and performing solid-liquid separation to obtain nano-zero-valent iron coated with manganese;

[0016] (2) mixing the manganese-coated nano-zero-valent iron, activated carbon, and ferrous sulfate to obtain modified nano-zero-valent iron with a core-shell structure;

[0017] The manganese salt solution is a manganese sulfate solution;

[0018] The core of the modified nano zero-valent iron with a core-shell structure is nano zero-valent iron, and the shell is manganese element and activated carbon.

[0019] The present invention creatively adds nano zero-valent iron to a manganese salt solution for reaction to obtain nano zero-valent iron wrapped with manganese, and then uniformly mixes the nano zero-valent iron wrapped with manganese, activated carbon, and ferrous sulfate to obtain modified nano zero-valent iron with a core-shell structure. The core of the modified nano zero-valent iron with the core-shell structure is nano zero-valent iron, and the shell is manganese element and activated carbon. The modified nano zero-valent iron with the core-shell structure has a clear surface contour, is basically in a uniform spherical granular shape, has a large specific surface area, excellent stability, good dispersion performance, and will not agglomerate. At the same time, the modified nano zero-valent iron with the core-shell structure and the activated carbon form a primary cell structure. Under the joint action of the surface Mn element and the double layer of activated carbon, electrons can be quickly released, and the material has excellent reduction adsorption performance and catalytic degradation performance, which significantly improves the rate at which the material releases free electrons, so that the catalytic degradation reaction can be achieved at room temperature and neutral conditions, and has broad application prospects.

[0020] The modified nano zero-valent iron with a core-shell structure mainly has peaks of Fe, C, Cl and S and a Fe2p spectrum peak, has many active sites, and can significantly improve its reduction adsorption performance and catalytic degradation performance.

[0021] The inventors of the present invention have found in a large number of studies that the type of the manganese salt solution has a significant impact on the effect. The present invention creatively uses manganese sulfate solution as the manganese salt solution. Manganese sulfate is cheap and easy to obtain, and has a low cost. The generated elemental manganese can play a catalytic role and regulate the particle size and morphology of nano zero-valent iron, thereby significantly improving the reduction adsorption performance and catalytic degradation performance. If it is not treated with manganese sulfate solution, it is difficult for perchlorate to react with nano zero-valent iron at room temperature. If other manganese salt solutions are used instead, the reduction adsorption performance and catalytic degradation performance will be significantly reduced. For example, manganese nitrate, nitrate, etc. are used. Acid radicals will react with nano zero-valent iron materials, resulting in the inhibition of the redox reaction between zero-valent iron and perchlorate, affecting the use effect. If manganese oxalate is used, manganese oxalate is slightly soluble in water under neutral pH conditions and cannot meet the concentration requirements in the solution. The oxalate ions and manganese ions in manganese oxalate are combined with each other through ionic bonds to form a stable lattice structure, which cannot effectively oxidize the iron surface material at room temperature, resulting in a poor manganese iron core-shell structure. In addition, ferrous oxalate and ferrous oxalate will form precipitates, which are complexed on the surface of nano zero-valent iron to hinder the reaction. Therefore, the use of other manganese salts will lead to a decrease in the reduction adsorption performance and catalytic degradation performance.

[0022] It should be noted that the present invention is not limited to the method of solid-liquid separation, and it may be, for example, filtration and / or centrifugation.

[0023] As a preferred embodiment of the present invention, the concentration of the manganese salt solution is 2 to 4 mol / L;

[0024] The mass ratio of the nano zero-valent iron and manganese salt solution is 1:(8-12).

[0025] The inventors of the present invention further explored the influence of the mass ratio of nano zero-valent iron and manganese salt solution on the effect. By controlling the mass ratio of nano zero-valent iron and manganese salt solution within the scope of the present invention, the generated elemental manganese can play a catalytic role, regulate the particle size and morphology of nano zero-valent iron, thereby significantly improving the reduction adsorption performance and catalytic degradation performance. If the mass ratio of nano zero-valent iron and manganese salt solution is too low (lower than 1:12), the catalytic effect is not obvious during the oxidation process. If the mass ratio of nano zero-valent iron and manganese salt solution is too high (higher than 1:8), the nano zero-valent iron is wrapped in a large amount, affecting the normal reaction of the nano zero-valent iron. Therefore, the present invention controls the mass ratio of nano zero-valent iron and manganese salt solution to be 1: (8~12).

[0026] As a preferred embodiment of the present invention, the mass ratio of the nano zero-valent iron and the manganese salt solution is 1:10. In particular, when the mass ratio of the nano zero-valent iron and the manganese salt solution is at this mass ratio, it can play an optimal catalytic role and regulate the particle size and morphology of the nano zero-valent iron, thereby more significantly improving the reduction adsorption performance and catalytic degradation performance.

[0027] As a preferred embodiment of the present invention, the reaction in step (1) is carried out at 10-30° C., the reaction time is 15-20 min, and the stirring rate during the reaction is 150-200 rpm.

[0028] As a preferred embodiment of the present invention, the mass ratio of the manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate is 1: (0.8-1.2): (0.15-0.25).

[0029] The present invention creatively combines manganese-wrapped nano zero-valent iron, activated carbon, and ferrous sulfate, and utilizes iron and activated carbon based on the iron-carbon microbattery principle to catalyze and improve reaction efficiency. At the same time, activated carbon has a highly porous structure and good adsorption properties, which can slow down the agglomeration of nano zero-valent iron. Among them, ferrous sulfate is a reducing agent, and an appropriate amount of ferrous sulfate can provide sufficient reducing ability to promote the reduction reaction of iron ions.

[0030] The present invention effectively improves the reduction adsorption performance and the catalytic degradation performance by controlling the mass ratio of nano zero-valent iron, activated carbon and ferrous sulfate. If activated carbon is not added, an iron-carbon microbattery cannot be formed, and the agglomeration phenomenon of nano zero-valent iron cannot be improved. If ferrous sulfate is not added, the nano zero-valent iron is easily oxidized and ineffective, and is not easy to preserve. At the same time, the inventors have found that if the mass ratio of manganese-coated nano zero-valent iron, activated carbon and ferrous sulfate deviates from the scope of the present invention, either the agglomeration phenomenon cannot be improved, or the nano zero-valent iron is easily oxidized and ineffective. Therefore, it is necessary to control the mass ratio of manganese-coated nano zero-valent iron, activated carbon and ferrous sulfate.

[0031] As a preferred embodiment of the present invention, the mass ratio of the manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate is 1:1:0.2. In particular, when the mass ratio of the manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate is at this mass ratio, the reduction adsorption performance and catalytic degradation performance are more significantly improved.

[0032] As a preferred embodiment of the present invention, the particle size of the activated carbon is 100 to 300 meshes.

[0033] The inventors of the present invention have found that when the particle size of the activated carbon is 100-300 mesh, it can effectively improve the agglomeration phenomenon of nano zero-valent iron. If the particle size of the activated carbon is too large, the effect of improving the agglomeration of nano zero-valent iron decreases. If the particle size of the activated carbon is too small, it is difficult to remove in water.

[0034] As a preferred embodiment of the present invention, the stirring rate in step (2) is 100 to 300 rpm, and the stirring time is 5 to 20 min.

[0035] The present invention also provides a modified nanometer zero-valent iron with a core-shell structure, which is prepared by the above-mentioned preparation method.

[0036] The present invention also provides an application of modified nano zero-valent iron with a core-shell structure in catalytic degradation of wastewater containing perchlorate.

[0037] The beneficial effects of the present invention are as follows: the present invention creatively adds nano zero-valent iron to a manganese salt solution for reaction to obtain nano zero-valent iron wrapped with manganese, and then evenly mixes the nano zero-valent iron wrapped with manganese, activated carbon, and ferrous sulfate to obtain modified nano zero-valent iron with a core-shell structure. The core of the modified nano zero-valent iron with the core-shell structure is nano zero-valent iron, and the shell is manganese element and activated carbon. The modified nano zero-valent iron with the core-shell structure has a clear surface contour, is basically in a uniform spherical granular shape, has a large specific surface area, is excellent in stability, has good dispersibility, and does not agglomerate. At the same time, the modified nano zero-valent iron with the core-shell structure and the activated carbon form a primary cell structure. Under the joint action of the surface Mn element and the double layer of activated carbon, the modified nano zero-valent iron can quickly release electrons, has excellent reduction adsorption performance and catalytic degradation performance, significantly improves the rate at which the material releases free electrons, enables the catalytic degradation reaction to be achieved at room temperature and under neutral conditions, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a scanning electron microscope micrograph analysis diagram of the material in Example 1 before and after the reaction.

[0039] Figure 2 This is a graph showing the changes in surface elements from XPS spectral analysis of the material in Example 1 before and after the reaction.

[0040] Figure 3 This is the XRD analysis diagram of GAC-nZVI changes before and after the reaction of the material in Example 1. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0043] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0044] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0045] Example 1

[0046] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0047] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0048] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0049] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0050] Example 2

[0051] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0052] (1) adding nano-zero-valent iron to a 2 mol / L manganese sulfate solution, stirring at 200 rpm for 18 min at 25° C., and centrifuging to obtain manganese-coated nano-zero-valent iron;

[0053] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:12;

[0054] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0055] Example 3

[0056] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0057] (1) adding nano-zero-valent iron to a 4 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain nano-zero-valent iron coated with manganese;

[0058] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:8;

[0059] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0060] Example 4

[0061] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0062] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0063] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0064] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate are uniformly stirred in a mass ratio of 1:1.2:0.25, wherein the stirring speed is 200 rpm and the stirring time is 10 min, thereby obtaining modified nano-zero-valent iron with a core-shell structure.

[0065] Example 5

[0066] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0067] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0068] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0069] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate are uniformly stirred in a mass ratio of 1:0.8:0.15, wherein the stirring speed is 200 rpm and the stirring time is 10 min, thereby obtaining modified nano-zero-valent iron with a core-shell structure.

[0070] Comparative Example 1

[0071] This comparative example is nano zero-valent iron.

[0072] Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 is not treated with a manganese sulfate solution, and the other aspects are the same.

[0074] The preparation method of the modified nano zero-valent iron of this comparative example comprises the following steps:

[0075] (1) Nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron.

[0076] Comparative Example 3

[0077] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses 3 mol / L manganese nitrate solution to replace 3 mol / L manganese sulfate solution, and the other conditions are the same.

[0078] Comparative Example 4

[0079] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses 0.125 mol / L (saturated solubility under neutral conditions at room temperature) manganese oxalate solution to replace 3 mol / L manganese sulfate solution, and the rest are the same.

[0080] Comparative Example 5

[0081] The difference between Comparative Example 5 and Example 1 is that the mass ratio of nano zero-valent iron to manganese sulfate solution is different, and the other contents are the same.

[0082] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0083] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0084] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:5;

[0085] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0086] Comparative Example 6

[0087] The difference between Comparative Example 6 and Example 1 is that the mass ratio of nano zero-valent iron to manganese sulfate solution is different, and the other contents are the same.

[0088] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0089] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0090] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:20;

[0091] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0092] Comparative Example 7

[0093] The difference between Comparative Example 7 and Example 1 is that Comparative Example 7 is not treated with activated carbon or ferrous sulfate, and the other aspects are the same.

[0094] A method for preparing modified nano zero-valent iron comprises the following steps:

[0095] (1) Add nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stir at 200 rpm for 18 min at 25° C., and centrifuge to obtain manganese-coated nano-zero-valent iron (modified nano-zero-valent iron).

[0096] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10.

[0097] Comparative Example 8

[0098] The difference between Comparative Example 8 and Example 1 is that no activated carbon is added in Comparative Example 8, and the other aspects are the same.

[0099] A method for preparing modified nano zero-valent iron comprises the following steps:

[0100] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0101] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0102] (2) The manganese-coated nano-zero-valent iron and ferrous sulfate were uniformly stirred at a mass ratio of 1:0.2, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron.

[0103] Comparative Example 9

[0104] The difference between Comparative Example 9 and Example 1 is that ferrous sulfate is not added in Comparative Example 9, and the other aspects are the same.

[0105] A method for preparing modified nano zero-valent iron comprises the following steps:

[0106] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0107] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0108] (2) The manganese-coated nano-zero-valent iron and 200-mesh activated carbon were uniformly stirred at a mass ratio of 1:1, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron.

[0109] Comparative Example 10

[0110] The difference between Comparative Example 10 and Example 1 is that the mass ratios of manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate are different, and the others are the same.

[0111] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0112] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0113] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0114] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:2:0.3, wherein the stirring speed was 200 rpm and the stirring time was 10 min, to obtain modified nano-zero-valent iron with a core-shell structure.

[0115] Comparative Example 11

[0116] The difference between Comparative Example 11 and Example 1 is that the mass ratios of manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate are different, and the others are the same.

[0117] A method for preparing modified nano zero-valent iron with a core-shell structure comprises the following steps:

[0118] (1) adding nano-zero-valent iron to a 3 mol / L manganese sulfate solution, stirring the mixture at 200 rpm for 18 min at 25° C., and centrifuging the mixture to obtain manganese-coated nano-zero-valent iron;

[0119] Among them, the mass ratio of nano zero-valent iron and manganese sulfate solution is 1:10;

[0120] (2) Manganese-coated nano-zero-valent iron, 200-mesh activated carbon, and ferrous sulfate were uniformly stirred in a mass ratio of 1:0.5:0.1, wherein the stirring speed was 200 rpm and the stirring time was 10 min to obtain modified nano-zero-valent iron with a core-shell structure.

[0121] Test Case

[0122] Test Example 1. Test results of degradation of perchlorate by the products prepared in the examples and comparative examples.

[0123] The products of the examples and comparative examples were respectively prepared into 14% aqueous solutions as purification solutions.

[0124] The test water sample is perchlorate enterprise water sample 1# (perchlorate concentration is 228.6 mg / L). For every 500 mL of water sample, 25 g of purified solution is added. The reaction is stirred for 8 hours at room temperature, the stirring speed is 250 rpm, and the precipitation time is 30 minutes. The filtered clear liquid is taken for detection. For the wastewater of the perchlorate production enterprise, the test results are shown in Table 1 (three groups of experiments are performed for each group of embodiments and comparative examples, and the results are averaged).

[0125] Table 1

[0126]

[0127]

[0128] It can be seen from Table 1 that the modified nano zero-valent iron with a core-shell structure described in the present invention has excellent reduction adsorption performance and catalytic degradation performance, and can effectively catalyze and adsorb perchlorate.

[0129] Comparing Examples 1 to 5, it can be seen that Example 1 is the best implementation of the present invention and has the best removal rate.

[0130] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention modifies the nano zero-valent iron, significantly improves the nano zero-valent iron's better adsorption performance and catalytic degradation performance, and significantly improves the removal rate of perchlorate wastewater.

[0131] By comparing Example 1 with Comparative Example 2, it can be seen that if the wastewater is not treated with manganese sulfate solution, the adsorption performance and catalytic degradation performance will be significantly reduced, thereby causing a significant decrease in the removal rate of perchlorate wastewater.

[0132] By comparing Example 1 with Comparative Examples 3 to 4, it can be seen that if the manganese sulfate solution of the present invention is replaced by other manganese salt solutions, the adsorption performance and catalytic degradation performance will be significantly reduced, thereby resulting in a significant decrease in the removal rate of perchlorate wastewater. In addition, the use of manganese oxalate will have a negative effect. This is because the solubility of manganese oxalate in neutral and slightly acidic solutions is very low, and the removal of perchlorate is degraded within the neutral range. Manganese oxalate has both an improving effect and an inhibitory effect. The reason for the reduction is that the amount is insufficient and the inhibitory effect is dominant.

[0133] By comparing Example 1 with Comparative Examples 5 to 6, it can be seen that the present invention further improves the adsorption performance and catalytic degradation performance by controlling the mass ratio of nano zero-valent iron and manganese sulfate solution, thereby further improving the removal rate of perchlorate wastewater.

[0134] By comparing Example 1 with Comparative Example 7, it can be seen that the present invention significantly improves the adsorption performance and catalytic degradation performance by using activated carbon and ferrous sulfate treatment, and significantly improves the removal rate of perchlorate wastewater.

[0135] By comparing Example 1 with Comparative Examples 8 to 9, it can be seen that both activated carbon and ferrous sulfate are indispensable. If any one of them is missing, the adsorption performance and catalytic degradation performance will be reduced, thereby causing a decrease in the removal rate of perchlorate wastewater.

[0136] By comparing Example 1 with Comparative Examples 10 to 11, it can be seen that the present invention controls the mass ratio of manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate, further improving the adsorption performance and catalytic degradation performance, thereby further improving the removal rate of perchlorate wastewater.

[0137] The microscopic morphology of the material before and after the reaction of the material in Example 1 was characterized and analyzed by scanning electron microscopy. Figure 1 As shown, Figure 1 The surface contour of the nano zero-valent iron material of a is clear before the reaction, and it is basically in the form of uniform spherical particles. Figure 1 b) The surface presents a large amount of villi. The formation of villi is mainly due to the iron oxides and iron hydroxides produced on the surface during the reaction, which greatly increases the specific surface area of ​​the material, improves the adsorption performance of the material, and provides favorable conditions for catalytic degradation.

[0138] The changes in chemical elements on the surface of the material of Example 1 before and after the reaction were analyzed by XPS spectroscopy. Figure 2 As shown, from Figure 2 a and Figure 2 From the overall spectrum in b, we can see that the peaks of Fe, C, Cl and S mainly exist on the surface of the material. Figure 2 a and Figure 2 b It can be seen that there are Fe2p spectral peaks on the surface of the material. Both peaks have slight changes after the reaction. Each Fe2p group can be ClO 4 - Provide active sites for the degradation of Figure 1 b and Figure 2 d The comparison shows that during the perchlorate degradation process, Cl ions bind to active sites on the material surface.

[0139] The GAC-nZVI change diagram of the material before and after the reaction of Example 1 was analyzed by XRD. Figure 3 As shown, from the XRD of the material, it can be seen that Fe 3 O 4 ,FeO,Fe 2 O 3 Both increased, indicating that while degrading perchlorate, the nano-zero-valent iron was oxidized into ferric oxide and ferrous oxide, that is, a redox reaction occurred in the solution, causing the surface structure of the nano-zero-valent iron to change.

[0140] Test Example 2. In order to further verify the effect of the present invention, experiments were conducted on wastewater from chlorate enterprises, firecracker factories, fireworks factories, fuse factories, and mountain ponds. The experimental methods were the same as those in Test Example 1. The test results are shown in Table 2.

[0141] Table 2

[0142]

[0143] As can be seen from Table 2, the modified nano zero-valent iron with a core-shell structure described in the present invention has a removal rate of more than 98% after reaction for wastewater from perchlorate production enterprises, and the effluent concentration is lower than 0.5 mg / L; for wastewater from firecracker factories, fireworks factories, and fuse factories (this type of wastewater is affected by interference factors, and the purification effect of perchlorate is slightly reduced), the removal rate after reaction is about 70%; for pond water, the removal rate after one reaction is about 85%. The main test data are shown in Table 1.

[0144] Test case 3.

[0145] From May 2023 to July 2023, pilot and industrial tests were carried out at Jinpeng Fireworks Factory in Liling City and Yixue Fireworks Factory in Liuyang City, respectively. The single-stage removal rate of perchlorate in the test process was 50%-67%. The test process is as follows: firecrackers and fireworks wastewater → regulating sedimentation tank → filter press to remove waste residue → primary reaction degradation → effluent reuse or discharge. The filter press uses a plate and frame filter press, and the filter press filtrate enters the primary, secondary, and tertiary reaction degradation. The reaction barrel is 300L. During the test, 25kg (14% concentration) of the solution configured in Example 1 is added to the reaction barrel, and the reaction time is 8 hours. The main test data are shown in Table 3.

[0146] Table 3

[0147]

[0148]

[0149] It can be seen from Table 3 that the modified nano zero-valent iron with a core-shell structure prepared in the present invention has excellent reduction adsorption performance and catalytic degradation performance, and can effectively catalyze and adsorb perchlorate.

[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing modified nano zero-valent iron with a core-shell structure, characterized in that: The following steps are involved: (1) adding nano-zero-valent iron to a manganese salt solution, reacting, and performing solid-liquid separation to obtain nano-zero-valent iron coated with manganese; (2) mixing the manganese-coated nano-zero-valent iron, activated carbon, and ferrous sulfate to obtain modified nano-zero-valent iron with a core-shell structure; The manganese salt solution is a manganese sulfate solution; The concentration of the manganese salt solution is 2-4 mol / L; the mass ratio of the nano zero-valent iron to the manganese salt solution is 1:(8-12); The mass ratio of the manganese-coated nano zero-valent iron, activated carbon, and ferrous sulfate is 1: (0.8-1.2): (0.15-0.25); The core of the modified nano zero-valent iron with a core-shell structure is nano zero-valent iron, and the shell is manganese element and activated carbon.

2. The method for preparing modified nano zero-valent iron with a core-shell structure according to claim 1, characterized in that: The reaction in step (1) is carried out at 10-30° C., the reaction time is 15-20 min, and the stirring rate during the reaction is 150-200 rpm.

3. The method for preparing modified nano zero-valent iron with a core-shell structure according to claim 1, characterized in that: The particle size of the activated carbon is 100 to 300 meshes.

4. The method for preparing modified nano zero-valent iron with a core-shell structure according to claim 1, characterized in that: The stirring rate in step (2) is 100 to 300 rpm, and the stirring time is 5 to 20 min.

5. A modified nano zero-valent iron with a core-shell structure, characterized in that: The preparation method is described in any one of claims 1 to 4.

6. Use of the modified nano zero-valent iron with a core-shell structure as claimed in claim 5 in catalytic degradation of wastewater containing perchlorate.

Citation Information

Patent Citations

  • Iron based-humus composite material and application thereof in soil heavy metal pollution control

    CN104971938A

  • Zero-valent iron and manganese composite modified activated carbon as well as preparation method and application thereof

    CN112934176A

  • Method for promoting nanometer zero-valent iron-manganese bimetallic material to remove organic pollutants in water body

    CN113943041A

  • Core-shell magnetic nano material as well as preparation method and application thereof

    CN114534683A

  • Zero-valent iron including lipids and manufacturing method thereof

    KR1020140104567A